2010
DOI: 10.1143/jjap.49.111202
|View full text |Cite
|
Sign up to set email alerts
|

Development of GaAs Gunn Diodes and Their Applications to Frequency Modulated Continuous Wave Radar

Abstract: In this work, we have designed and fabricated the GaAs Gunn diodes for a 94 GHz waveguide voltage controlled oscillator (VCO) which is one of the important parts in a frequency modulated continuous wave (FMCW) radar application. For fabrication of the high power GaAs Gunn diodes, we adopted a graded gap injector which enhances the output power and conversion efficiency by effectively removing the dead-zone. We have measured RF characteristics of the fabricated GaAs Gunn diodes. The operating current, oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For instance GaAs-based Gunn diodes are made with frequencies up to 200 GHz, whereas GaN-based ones can reach up to 3 THz 37 . Furthermore, both Esaki and Gunn diodes use NDR for applications as oscillators, amplifiers, frequency converters, and detectors 38,39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance GaAs-based Gunn diodes are made with frequencies up to 200 GHz, whereas GaN-based ones can reach up to 3 THz 37 . Furthermore, both Esaki and Gunn diodes use NDR for applications as oscillators, amplifiers, frequency converters, and detectors 38,39 .…”
Section: Introductionmentioning
confidence: 99%
“…The methods are incorporated into the code of Atomistic Tool-Kit (ATK) 51 . While debates about the origins and mechanisms yielding NDR are still active, the so-far achieved findings can be categorized into three possible groups: (i) Two-valley model has been successful to explain the Gunn effect as stated above 3639 ; (ii) Suppression of resonant band/channel at Fermi level which is the case of molecular junctions 4045 . Using ATK, Fan and coworkers 52 demonstrated that a single C 60 -molecule in a nanodevice can yield NDR controllable by shape deformation of molecule and specifically its interactions with the leads.…”
Section: Introductionmentioning
confidence: 99%
“…For applications such as vehicle collision avoidance systems and military radar sensors, frequency modulated continuous wave (FMCW) radar technology operating in the W‐band is an excellent solution. The improved performance of FMCW radar system necessitates the development of a waveguide VCO with high linearity and a wide bandwidth, which in turn demands the need for a high‐performance varactor diode . One very attractive feature of varactor diodes is their ability to electronically tune a given circuit to different frequencies by changing the reverse‐bias conditions .…”
Section: Introductionmentioning
confidence: 99%